The Computational Linguistic Term: A Descriptive Approach to the Efforts of the King Abdullah bin Abdulaziz International Center for the Service of the Arabic Language - hamida, hassina; Kaddour Jebbar, Jamila; derkaoui, mektar (El Omda in Linguistics and Discourse Analysis, 2026)
:Abstract This research aims to introduce the efforts of the" king Abdullah Bin Abdulaziz International Center for Arabic Language Service" in promoting computational linguistic terminology work. The study reviews collection of publications issued by the center related to the field of computational linguistics, focusing on the extraction of various computational linguistic terms across different domains such as phonetics, morphology, syntax, sematics, and text analysis. Additionally, the research highlights the formation of a specialized computational linguistic .terminological field based on the center's work, encompassing more than sixty terms